To solve the equation \( \frac{b}{-2} + 26 = 3 \), follow these steps:
-
Subtract 26 from both sides: \[ \frac{b}{-2} = 3 - 26 \] \[ \frac{b}{-2} = -23 \]
-
Multiply both sides by -2 to solve for \( b \): \[ b = -23 \times -2 \] \[ b = 46 \]
Since 46 is not one of the answer choices (31, 72, 75), let's check our calculations one more time to make sure we did it correctly.
The calculations have been confirmed. There seems to have been a misunderstanding of the question regarding the expected answer choices. The solution to the equation as per the calculations provided is indeed \( b = 46 \), which is not listed in the options.
Would you like to check the inputs or parameters of the question? If you are looking for something specific or another problem, please let me know!